Efeitos do alongamento e do aquecimento no desempenho isocinético e na atividade eletromiográfica do músculo bíceps femoral ensaio clínico randomizado - Amaro, Ivy Marques (2010)
To evaluate the effects of warm-up and stretching, singly or combined, on isokinetic performance and electromyographic activity of the biceps femoris. Materials and methods: Sixty-four volunteers of both sexes, with mean age of 23,1 ± 3,5 years and mean body mass index of 23,5 ± 2,5 Kg/m2 were randomly assigned into 4 groups: control, warm-up (stationary bicycle for 10 minutes), stretching (4 sets of 30 seconds of hamstring muscles static stretching) and warm-up + stretching. All the volunteers were submitted to evaluation pre and post-intervention of the muscle latency time and biceps femoris RMS and the passive torque, peak torque and power of the hamstring muscles. Results: The warm-up + stretching group had reduction of muscle latency time. There was a reduction of RMS during passive torque evaluation in stretching group. The RMS during isometric evaluation was reduced in all experimental groups. The RMS during eccentric evaluation showed reduction in control and warm-up + stretching groups. The passive torque and the eccentric peak torque had no significant differences pre to post-intervention in any group. There was reduction in isometric peak torque in all groups. Conclusion: The warm-up and stretching, when applied in combination can reduce the muscle latency time; stretching protocol promoted neural changes; the protocols used did not alter the muscle viscoelastic properties